SOSIALISASI PEMANFAATAN INTERNET SEHAT UNTUK MENINGKATKAN PENGETAHUAN TENTANG BAHAYA CYBER BULLYING PADA SISWA DI SMK CITRA NUSANTARA PANONGAN - Lely Panca Andriyanto; Nanang Nanang; Meidy Fajar Wahyu (KOMMAS: Jurnal Pengabdian Kepada Masyarakat, 2022)
The development of internet technology is growing so rapidly. The internet has become an inseparable part of modern human life. From year to year the internet in Indonesia is growing very fast. Currently the internet is a primary need because it fulfills almost all areas of life. From the smallest thing to the most complex, everything can be done with the internet. Behind the benefits are so great, the internet has a negative impact. One of the negative impacts is cyber crime. In Indonesia, the number of internet users is dominated by teenagers or students aged 15-19 years. Internet crimes that often befall students are Cyber Bullying. From the problems that occurred, the community service team has carried out service activities with the theme of Socializing the Use of Healthy Internet to increase knowledge about the dangers of Cyber Bullying in students at SMK Citra Nusantara Panongan. This activity aims to provide counseling to students and vocational school students how to use internet technology wisely so that students avoid Cyber Bullying.